Multi-scale Seismic Measurements for CO2 Monitoring in an EOR/CCUS Project. (July 2017) - El-kaseeh, George; Will, Robert; Balch, Robert; Grigg, Reid
Abstract: Acquiring multi-scale seismic measurements – 3D surface seismic, vertical seismic profiles (VSPs), and cross-well seismic data – comes with high cost and can be an operationally challenging endeavour, particularly in an oilfield under active enhanced oil recovery (EOR) management, as is the case with the Farnsworth Unit (FWU) EOR Field Project. The three aforementioned measurements were implemented in the FWU geophysical program, and utilized in conjunction with downhole measurements to address multiple site characterization and monitoring objectives for both EOR optimization and carbon dioxide (CO2 ) sequestration and monitoring. The three geophysical methods will be discussed in this paper.